Implementation of Religious Culture and Its Implications for Students' Religious Development in Junior High School 10 Bandung - Nurdiana, Agus (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2023)
This research aims to describe the development of students' religion at SMP Negeri 10 Bandung. This research was motivated by the large number of immoral cases committed by the younger generation, such as drug cases, free sex, and so on. These various problems cannot be solved, but by returning to religious teachings, one way is by making religious education more effective in schools, one of which is through religious culture. This research is a type of qualitative research. The research approach used is phenomenological (meaning of existence). The informants for this research consisted of the school principal, all Islamic religious education teachers, several teachers other than Islamic religious education teachers, and students. The results of the research show that the implementation of student religious formation through religious culture at SMP Negeri 10 Bandung has gone well and is programmed, and carried out by the school as a complete educational institution with lessons related to the development of religious culture in schools and community activities carried out by Rohis (Islamic Spirituality) as an extracurricular activity at a special shade school. This success can be achieved because of the efforts of the principal and the support of the entire school community by showing commitment, each of which occurs together and supports each other.